2004
DOI: 10.1097/01.mcg.0000139058.43414.a1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Mucosa-Associated Lymphoid Tissue Lymphoma and Hepatocellular Carcinoma in a Patient With Hepatitis B Virus Infection

Abstract: Primary hepatic mucosa-associated lymphoid tissue (MALT) lymphoma is an extremely rare disease. A 65-year-old female patient with chronic hepatitis B presented with multiple solid masses in segment (S) 4, S5, and S6 of the liver. The nodule in S5 was diagnosed preoperatively as hepatocellular carcinoma by computed tomography, magnetic resonance imaging, and angiography. The nodule in S4 was initially interpreted as lymphoid follicles by needle biopsy. Segmentectomy of S5 and partial resection of S6 were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
1
22
0
4
Order By: Relevance
“…Whether HCV infection can lead to hepatic MALT lymphoma or not remains unclear. There are only 2 reported cases of MALT lymphoma (15,16) with HBV infection. The correlation between HBV and hepatic MALT lymphoma remains unclear, although hepatic MALT lymphoma is thought to be associated with specific immune reactions or autoimmune disorders.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…Whether HCV infection can lead to hepatic MALT lymphoma or not remains unclear. There are only 2 reported cases of MALT lymphoma (15,16) with HBV infection. The correlation between HBV and hepatic MALT lymphoma remains unclear, although hepatic MALT lymphoma is thought to be associated with specific immune reactions or autoimmune disorders.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…Talamo et al[ 3] were the first to report a case of simultaneous occurrence of primary hepatic lymphoma and HCC. Takeshima et al [4 ]reported a patient with hepatic occurrence of mucosa-associated lymphoid tissue lymphoma together with HCC. These 2 cases showed no evidence of extrahepatic involvement by lymphoma, and they are considered to represent primary hepatic lymphoma, defined as confined to the liver with no evidence of lymphomatous involvement in the spleen, bone marrow, or other lymphoid structures.…”
Section: Discussionmentioning
confidence: 99%
“…According to the report on the focal liver lesions detected by imaging techniques in 414 patients with non-Hodgkin’s lymphoma (NHL) [2], only 1 case presented with simultaneous coexistence with NHL and HCC. We know of only four previously reported similar cases [3,4,5,6], all associated with hepatitis B virus (HBV) infection. How HBV and development of lymphoma are related is not known, although some reports have suggested a possible pathogenetic role of HBV in the development of hematologic malignant diseases [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that direct effects of HCV on hepatocytes, as well as chronic inflammation, contribute to the evolution of HCC. In spite of the putative etiologic role of HCV in both HCC and lymphoma, and the primary localization of HCV infection in the liver, there are few case reports of the simultaneous occurrence of hepatic lymphoma and HCC [2,3,4,5,6,7]. Of the 6 previously reported cases, 3 were associated with hepatitis B virus, 1 with HCV, 1 with neither and 1 was not specified.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest link between HCV and lymphoma has been shown in splenic marginal zone lymphoma, but other lymphoma subtypes have also been associated with HCV. Six cases of concurrent hepatic lymphoma and HCC have been reported [2,3,4,5,6,7]. The lymphoma subtypes reported included diffuse large B-cell and mucosa-associated lymphoid tissue.…”
Section: Introductionmentioning
confidence: 99%